28 day post-operative persisted hypercoagulability after surgery for benign diseases: a prospective cohort study. Issue 1 (December 2016) - Ulrych, Jan; Kvasnicka, Tomas; Fryba, Vladimir; Komarc, Martin; Malikova, Ivana; Burget, Filip; Brzezkova, Radka; Kvasnicka, Jan; Krska, Zdenek; Kvasnicka, Jan
Abstract Background Surgery for benign disease is associated with a low-risk of developing venous thromboembolism (VTE). Despite a relatively low incidence of postoperative VTE in patients after elective cholecystectomy and abdominal hernia repair there are data proving hypercoagulability in the early postoperative period. We focused on assessment of the systemic inflammatory response and coagulation status in these surgical patients after hospital discharge. Methods Prospectively, patients who underwent surgery for benign disease were included. Two hundred sixteen patients were enrolled - 90 patients in laparoscopic cholecystectomy (LC) group and 126 patients in hernia surgery (HS) group. Risk assessment of VTE according to the Caprini risk assessment model was performed in all patients. Prevalence of VTE in postoperative period was observed. Markers of systemic inflammatory response (IL-6, CRP, α-1-acid glycoprotein, transferrin) and coagulation markers (PLT, fibrinogen, prothrombin fragment F1 + 2 and D-dimer) were measured before surgery, on 7–10th postoperative day and on 28–30th postoperative day. Results Clinically apparent deep vein thrombosis was diagnosed in only one patient - 0.46 %. Statistically significant elevation of inflammatory markers IL-6, CRP and α-1-acid glycoprotein (p < 0.001; all) were proved in both groups of patients on 7–10th postoperative day. Statistically significant elevation of coagulation markers PLT, fibrinogen, prothrombin fragment F1 + 2 and D-dimer (p < 0.001; all) were proved in LC and HS groups on 7–10th postoperative day. No statistical difference was observed in IL-6, CRP and α-1-acid glycoprotein levels a month after surgery as compared with preoperative levels within each group. Statistically significant elevation of fibrinogen and prothrombin fragment F1 + 2 levels (p < 0.001; both) persisted on 28–30th postoperative day in both groups. Persisted elevation of D-dimer levels was proved only in HS group (p < 0.001), not in LC group (p = 0.138), a month after surgery. Conclusions Activated systemic inflammatory response and hypercoagulable condition were verified in patients after laparoscopic cholecystectomy and hernia surgery after their hospital discharge. Hypercoagulability persisted even a month after surgery. Nevertheless, we observed very low prevalence of clinically apparent VTE in patients with in-hospital postoperative VTE prophylaxis. Trial registration Trials of the Czech Ministry of Health No.RVO-VFN64165 andNT 13251-4 .